Information Frictions among Firms and Households - Sebastian Link; Andreas Peichl; Christopher Roth; Johannes Wohlfart (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We leverage survey data from Germany, Italy, and the US to document several novel stylized facts about the extent of information frictions among firms and households. First, firms' expectations about the central bank policy rate, inflation, and aggregate unemployment are more aligned with expert forecasts and less dispersed than households'. Second, there is substantially more heterogeneity in information frictions within households than within firms. Third, consistent with firms having stronger priors, they update their policy rate expectations significantly less compared to households when provided with an expert forecast. Our results have important implications for modeling heterogeneity in macroeconomic models.
Keywords: D83; D84; E71; 330; information frictions; firms; households; expectation formation; interest rates